Taxonomic corrections of certain verified non-indigenous reptiles from Florida reported by Krysko et al. (2011) - Krysko, Kenneth L.; Somma, Louis A.; Rochford, Michael R.; Gillette, Christopher R.; Enge, Kevin M.; Cueva, Daniel (Zootaxa, 2012)
In a recent issue of Zootaxa, Krysko et al. (2011) compiled and evaluated vouchers (i.e., specimens and photographs), and confirmed three intercepted and 137 introduced species of non-indigenous amphibians and reptiles in Florida from 1863 through 2010.  Trying to improve upon previous methodologies of reporting new non-indigenous species, we stressed the importance of providing all known data along with vouchers to help keep numbers of species consistent, accurately identify species, document when and where a particular species is found, and identify the invasion pathway and current invasion stage of each species.  High resolution digital images of each of the 83 newly confirmed taxa were registered in MorphoBank (www.morphobank.org; project number p536).  Physical voucher specimens are always preferred over photographs, as it can be quite difficult to accurately identify species that are morphologically similar or cryptic, especially in species that we are unfamiliar with or may originate in different countries.  In this paper we attempt to correct the species names of four taxa as well as the family and authority names attributed to one species.